Observation on therapeutic effect of acupoint application and massage technique in treating constipation after cerebral infarction (穴位贴敷与推拿手法治疗脑梗死后便秘疗效观察) - GUO Haijiao (果海姣); LIU Ganlu (刘甘露); MA Xiaoxu (马晓旭); SU Rong (苏容); CHEN Cheng (陈程); MA Dayong (马大勇); HU Zhe (胡哲); LIU Wenli (刘文丽); GENG Qingwen (耿庆文) (Association of Integrative Nursing, 2022)
Objective To observe the curative effect of massage technique and acupoint application in treating constipation after stroke. Methods Totally 78 patients with acute constipation after cerebral infarction were selected, divided into control group, acupoint application group (Acupoint application group) and massage treatment group (massage group), among which 22 patients in control group, 31 patients in application group and 25 patients in massage group. The control group patients received integrative medicine treatment and nursing. On this basis, the massage group patients received acupoint massage technique; the Acupoint application group patients were given Traditional Chinese Medicine Shenque acupoint application. The defecation situation of the three groups was observed daily for 2 weeks, and the defecation frequency of the three groups was compared with the 7th and 14th day of treatment. Barthel Index was used to evaluate the activity of daily living of patients before discharge from hospital. Results In the first week of treatment, the defecation frequency was higher in the massage group than that in the massage group and control group (P<0. 05). In the second week of treatment, the defecation frequency was higher in the massage group than that in the control group (P<0. 05). Increased frequency of defecation was reported in three groups in the second week of treatment compared with that in the first week of treatment. All three groups showed a trend of higher Barthel index before discharge form hospital. Conclusion Acupoint therapy and constipation massage treatment can improve the defecation frequency of constipation patients after stroke, especially acupoint therapy. (目的 观察穴位贴敷与推拿治疗脑梗死后便秘的 效果。方法 筛选脑梗死后便秘的患者78例, 分为对照组、穴位贴敷组(贴敷组)和推拿组(推拿组), 三组患者人数分别为22例、31例和25例。对照组采用常规中西医治疗及护理; 在此基础上, 贴敷组患者采中药神阙穴贴敷; 推拿组患者采用穴位推拿手法。干预2周, 每日观察三组患者的排便情况, 于治疗第7和14天对比三组患者的排便频率。采用Barthel指数(BI)评价患者日常生活活动能力。结果 治疗第1周, 贴敷组患者排便频率高于推拿组和对照组, 差异有统计学意义(P＜0. 05); 治疗第2周, 贴敷组患者排便频率高于同期的对照组(P＜0. 05); 三组治疗第2周排便频率均较第1周均升高。三组患者出院时BI均较入院时均升高。结论 穴位贴敷治疗和推拿手法治疗能改善脑梗死后便秘患者排便频率, 其中穴位贴敷治疗效果更明显。)